An in situ XPS study of growth of ITO on amorphous hydrogenated Si: Initial stages of heterojunction formation upon processing of ITO/a‐Si:H based solar cell structures. Issue 1 (24th November 2014) - Diplas, Spyros; Romanyuk, Andriy; Thøgersen, Annett; Ulyashin, Alexander
<x xml:space="preserve">Abstract</x> In this work we studied the interface growth upon deposition of indium‐tin oxide (ITO) on amorphous hydrogenated Si (a‐Si:H)/crystalline Si (c‐Si) structures. The analysis methods used were X‐ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy (UPS) in combination with in situ film growth with magnetron sputtering. The analysis was complemented with transmission electron microscopy (TEM) of the deposited films. The sputtering equipment was attached to the XPS spectrometer and hence early stage film growth was observed without breaking the vacuum. It was shown that during early deposition stages ITO is reduced by a‐Si:H. The reduction is accompanied with formation of metallic In and Sn at the interface. Formation of Sn is more enhanced on a‐Si substrates whilst formation of In is more dominant on c‐Si substrates. The reduction effect is less intense for amorphous hydrogenated Si as compared to crystalline Si and this is attributed to stronger presence of dangling bonds in the latter than the former.